Application of quality control circle activities to improve the correct rate of postoperative respiratory muscle training in patients undergoing surgery for lung cancer (提高肺癌患者术后呼吸功能锻炼正确执行率的品管圈实践) - GAO Caili (高彩丽); PENG Ya (彭娅); WU Qiaomei (吴巧梅); ZHU Lifang (朱莉芳) (Association of Integrative Nursing, 2021)
Objective To evaluate the quality control circle (QCC) activities in improvement of the correct rate of postoperative respiratory muscle training in patients undergoing surgery for lung cancer. Methods A QCC group was set up, and a series of activities based on QCC theory were carried out including theme identification, plan making, status investigation, factor analysis, countermeasures and implementation. Results The correct rate of postoperative respiratory muscle training increased from 53. 33% to 79. 17%, with a target achievement ratio of 104. 87% and progress ratio of 48. 6%. Nurses' comprehensive ability were enhanced after implementation of QCC activities. Conclusion The QCC is effective to improve of the correct rate of postoperative respiratory muscle training and quality of nursing for patients undergoing surgery for lung cancer. (目的 探讨品管圈(QCC)活动提升肺癌患者术后呼吸功能锻炼正确执行率中的效果。方法 成立品管圈活动小组, 按照QCC理论进行主题选定、活动计划、现状把握、要因分析、对策拟定与实施等活动, 并评估活动前后的相关指标。结果 开展QCC活动后, 肺癌患者术后呼吸锻炼正确执行率由开展前的53. 33%提高至开展后的79. 17%。本次活动目标达成率104. 87%, 进步率48. 45%, 护士综合能力也得到提高。结论 开展QCC活动有利于提高肺癌患者术后呼吸功能锻炼正确执行率, 有利于提高护理质量。)